Jawaban:
1.809
Penjelasan dengan langkah-langkah:
f(y) = 3(y) x y² + y(y)
f(9) = 3(9) x 8² + 9(9)
f(9) = 27 x 64 + 81
f(9) = 1.728 + 81
f(9) = 1.809
f(y) = 3(y) × y² + y(y)
f(9) = 3(9) × 9² + 9(9)
f(9) = (3 × 9) × (9 × 9) + (9 × 9)
f(9) = 27 × 81 + 81
f(9) = 2.187 + 81
f(9) = 2.268
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Jawaban:
1.809
Penjelasan dengan langkah-langkah:
f(y) = 3(y) x y² + y(y)
f(9) = 3(9) x 8² + 9(9)
f(9) = 27 x 64 + 81
f(9) = 1.728 + 81
f(9) = 1.809
f(y) = 3(y) × y² + y(y)
f(9) = 3(9) × 9² + 9(9)
f(9) = (3 × 9) × (9 × 9) + (9 × 9)
f(9) = 27 × 81 + 81
f(9) = 2.187 + 81
f(9) = 2.268